Trends and Directions in Life Skills Assessment for Elementary School Students from a Guidance and Counseling Perspective: A Systematic Literature Review - Irma Ari Irawan, Tb Moh; Yudha, Eka Sakti; Rusmana, Nandang; Khairuddin, Ahmad Zulfadhli (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2026)
Life skills education plays a crucial role in supporting students' academic achievement, social-emotional well-being, and adaptive capacity from an early age. However, systematic reviews on valid life skills assessment instruments that are developmentally appropriate for elementary school students from a guidance and counseling perspective remain limited. This study aims to systematically examine the trends and directions in the development of life skills assessment instruments for elementary school students from a guidance and counseling perspective. The method employed was a Systematic Literature Review following the PRISMA 2020 guidelines. Literature searches were conducted across four major databases namely Scopus, Web of Science, ERIC, and PsycINFO, covering articles published between 2010 and 2025, yielding a total of 1,020 records. Through a rigorous process of identification, screening, and eligibility assessment, 90 articles met the inclusion criteria and were analyzed using thematic synthesis techniques. The findings indicate that life skills assessment instruments for elementary school students primarily measure domains of social-interpersonal skills, emotional regulation, self-management, and problem-solving, while aspects related to career awareness and contextual adaptability receive relatively limited attention. Self-report scales and teacher ratings are the most dominant types of instruments, whereas performance-based and digital assessments are still emerging and remain underutilized. Geographically, instrument development is predominantly concentrated in Global North countries, raising concerns regarding cultural relevance and measurement equity. These findings underscore the importance of developing life skills assessment instruments that are developmentally sensitive, culturally responsive, and aligned with the needs of guidance and counseling services in elementary schools.